Getting Ready to Teach Online: A Malaysian Experience - Chan, Chang Tik (INTI University College, 2007)
Online discussion in a forum plays a crucial role in the delivery of distance-learning materials. We should not use the learning management system as depository of contents, but as a platform for active exchange of ideas and collective reflections In order to generate new knowledge. This paper looks into online training of lecturers using” e-tivities” to promote online discussions. The training lasted ten weeks and the participants learned the key skills needed to host online discussions and function as e-instructors. This paper also deals with the various aspects of content development for distance-learning modules and the problems encountered.